Application of Smart Apps Creator as Social Studies Learning Media in Class VII Market Materials - Yusup, Yusup; Subiyakto, Bambang; Sari, Raihanah; Ilhami, M. Ridha; Syarifuddin, Syarifuddin (Program Studi Pendidikan IPS, 2024)
Smart Apps Creator is used by educators as Interactive Multimedia to become an interesting technology-based media, so that the learning process is easier and more fun so that it can motivate students while learning. The purpose is to describe the efforts of educators in using technology in making interesting innovations in the learning process for students in class VII on MTs. Raudhatul Islamiyah. The research method used is a qualitative method with the aim of explaining the creation and application of interactive multimedia in Market Material in Class VII at MTs. Raudhatul Islamiyah. The subjects of the study were social studies educators and grade VII learners. Observation is carried out by making direct observations of the object of research, while interviews involve interaction with individuals related to the research. Documentation, in this study takes data from certain documents that are relevant to the research. After completing collecting data, the next stage is analyzing using descriptive analysis methods. This analysis process includes data reduction, data presentation, and conclusions, which collectively help create a comprehensive illustration. The results and discussion of the research is the creation and application of Interactive Multimedia Social Studies Learning from local content Lok Baintan Floating Market using the Smart Apps Creator application by educators in the learning process Market Material for grade VII MTs students. Raudhatul Islamiyah can contribute to the development of innovative and effective learning strategies at the secondary education level. The conclusion that can be drawn from this study is that the application of interactive multimedia social studies learning by social studies teachers using Smart Apps Creator makes learning more effective and efficient in accordance with the objectives for education.